Getting to Education to Get to Health: A Culture of Health Intervention in Orange, New Jersey. Issue 1 (8th March 2021) - McCaffrey, Katherine T.; Fullilove, Mindy Thomson
Abstract: In this essay, we tackle the challenge of adapting the dominant way we think about health in the United States—through an individualistic, technocratic, biomedical lens—to address social problems rooted in structural inequality. As scholar activists, the authors participated in a coalition effort to improve community health in a postindustrial New Jersey city. Adopting a social determinants of health perspective, we describe efforts to move discourse away from wellness and toward a deeper understanding of the role of education and learning in building a "culture of health." The essay discusses how this structural analysis of health competed with much more narrow cultural understandings of education and health rooted in a pervasive wellness ideology. Coalition success hinged on correctly identifying the obstacles to health and learning in the community as understood by community members: violence emerged as a pressing obstacle that impeded both learning and health. Once we clarified a shared understanding of health as learning and a common understanding of violence as the most immediate obstacle to health as learning—our coalition was energized and made progress.